Impact of Volcanoes National Park conservation on local food security - Madeleine Nyiratuza; Aristide Maniriho; Felix L. M. Ming’ate; Caleb Mireri (Cogent Social Sciences)
This study employed mixed methods, including a survey of 400 households, 21 key informants, and 10 focus groups conducted in January-March 2019, to evaluate the contribution of Volcanoes National Park (VNP) conservation to local food security in Rwanda. Data was collected from communities within 0-5 km and 5-10 km park buffers, facilitating distance-based comparisons. Food security status was assessed using the Consolidated Approach to Reporting Indicators of Food Security. Despite government attention to food security, its integration into VNP conservation remains minimal. Shockingly, 71% of local residents experience food insecurity, concentrated within the 0-5 km buffer. Interestingly, while only 38% of households directly benefit from park conservation, 72% of these beneficiaries reside within the 0-5 km zone. This suggests that community conservation and revenue-sharing programs are disproportionately funded at the park’s edge, where human pressure on resources is most significant. These findings highlight the need for policy and strategy amendments, as well as revisions to the park management plan, to effectively integrate food security concerns into VNP conservation efforts. Linking a specified percentage of revenue-sharing funds to participation in relevant food security programs, co-managing land for conservation and community needs, weaving food aid into safety nets for vulnerable groups, prompt wildlife damage payouts for secured livelihoods and fostered coexistence, and skill training and microloans for diversifying income and curbing poaching are crucial for enhancing food security among households around the VNP.